Faktor Penentu Penerapan Akuntansi Digital pada UMKM: Intervensi Pemerintah sebagai Variabel Pemoderasi - Aryanto; Ida Farida (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Technological advance and intense business competition require MSME actors to be able to take advantage of technology in managing their business, one of which is by applying digital accounting. The purpose of this study is to analyze the factors that determine MSME actors in implementing digital accounting with government intervention as a moderating variable. The factors that will be analyzed in this study use the Technology-Organization-Environment (TOE) Framework. The study was conducted on MSME actors in the City and Regency of Tegal with a sampling technique in the form of accidental sampling. The research obtained is in the form of primary data with the technique of collecting it through a questionnaire. The data that has been collected was analyzed using SmartPLS 3.0. The result showed that compatibility, owner commitment, and competitive pressure had a significant effect on the application of digital accounting, while relative advantage had no significant effect on the application of digital accounting. Government intervention is not able to moderate in this research model. The result of this study is expected to be used by the government as consideration for policy making related to the development of a digital financial ecosystem fo MSMEs in the City and Regency of Tegal.